Trade unions as knowledgeable participants in workplace innovation. Issue 9 (5th August 2014) - Totterdill, Peter; Exton, Rosemary
Abstract : Purpose: – This article aims to demonstrate that trade unions possess unique knowledge of how organisations really work and that they are repositories of experience embracing many different situations and stretching over many years. Closing the gap between best practice and common practice needs knowledgeable advocates to actively demonstrate what workplace innovation is and how it benefits organisations and individuals. Design/methodology/approach: – This article demonstrates that trade unions possess unique knowledge of how organisations really work and that they are repositories of experience embracing many different situations and stretching over many years. Yet, this experience and understanding is often an underused resource in workplaces. Findings: – At the frontline, union representatives can release their members' tacit knowledge and ideas for improvement and innovation. At strategic level, unions can deliver robust advice and consultancy, securing trust from employees and employers alike. Actively involving unions in dialogue about challenges and opportunities is the key to unlocking this potential. Practical implications: – The paper draws upon examples of collaborative working and the role of unions from the USA, Ireland and Norway, while a more detailed analysis of the "Danish Experience" demonstrates how Ideas, high levels of knowledge and strong relationships between unions and employers able to handle both shared and conflicting interests, impacts on trade unions ability to "stimulate, resource and sustain workplace innovation". Originality/value: – The paper concludes with a call to action showing how a mass movement of workplace innovation can be achieved through shared learning case studies and resources and from the creation of the European Workplace Innovation Network Knowledge Bank to help people to share their knowledge and experience.